Contextualisation of Selected Israelite Sacred Cultic Elements and Practices in Cherubim and Seraphim Churches, in Ibadan, Nigeria (2014)
The activities of n w m Cherubim and Seraphim Church (OIMCandSC) in Ibadan are connected with the practices and elements of the ancient Israelite religion from which the church took its root. Existing studies have examined the activities from a liturgical point of view, but have not adequately explored how they have been contextualised. This study, therefore, investigated the adoption of selected Israelite sacred cultic practices, namely, ritual cleansing, scapegoatism and sacred elements in OIMCandSC in Ibadan with a view to establishing their benefits and significance for members. The study adopted Adamo’s African cultural hermeneutics, which approaches the Bible from a premeditated Afrocentric perspective. The historical-critical method, which articulates the socio-cultural forces that shaped the biblical text, was used. Focus group discussions were held with 11 different groups, comprising ten members and two leaders from OIMCandSC branches in Ibadan. Participant observation method was also utilised. Three hundred and twenty-seven copies of a questionnaire were administered to seven founders, 30 clerics, 88 heads of groups and 202 members in 28 branches across all the local government areas in Ibadanland. Data were subjected to exegetical analysis and percentages. Some elements and practices inherent in Israelite religion have been contextually grounded in different forms in OIMCandSC. Ritual cleansing-(Lev.12; 15), a common practice in ancient Israelite religion, provided inner-spiritual purity for women who had completed their menstrual cycle and individuals cured of diseases. In OIMCandSC, spiritual and curative baths were performed by the prophets for individuals after ailments; and women after child delivery. A total of 95.4% of the respondents believed that ritual cleansing helped in addressing problems of chronic diseases, spiritual impurities which were obstacles to success, and misfortune. Scapegoatism-Lev.16:20-34 in Israelite religion was the practice whereby communal misdemeanour was symbolically transferred to a he-goat. In OIMCandSC, a he-goat was slaughtered in order to ward off death; this was tagged femiremi (life-for-life) because a sick person’s untimely death was transferred to the scapegoat. Sacred elements-Ex.40:9-15/Lev.14:15-18 in Israelite cultic activities included the use of consecrated water, candles and oil to encounter God’s power. Similarly, in OIMCandSC, the sick and private properties were anointed with oil for healing and protection, respectively. Consecrated water was sprinkled on residential, business and worship premises for protection and purification, while candle was used to enhance access into the supersensible realms. revalence of Israelite cultic practices in I andS was attributed by . of the respondents to the similarities between Israelite and or b worldviews. Moreover, 82.7% believed they were useful resources for transmitting religious ideas. Likewise, 94.5% agreed that they offered psychological relief because they provided a point of contact between the physical and mental belief spaces. Israelite cultic activities, manifesting as curative baths, symbolic death transfer and sacred elements confirming the patterning of n w m Cherubim and Seraphim Church after Old Testament, have been effectively utilised in the church to contextually ground their brand of Christian faith. These practices have helped in addressing the problems of chronic diseases; ward off untimely death, misfortune and made worship meaningful to members